Structure-controlled optical thermoresponse in Ruddlesden-Popper layered perovskites - Cortecchia, Daniele (2018)
Ruddlesden-Popper perovskites are highly attractive for light-emitting and photonic applications. In these exceptionally deformable frameworks, structural properties strongly impact on the energetic landscape of the material; thus, it is crucial to establish a correlation between the structure and optoelectronic characteristics. Here, we study the structural transformations induced by phase transitions in the butylammonium-based series (BA)2(MA)n−1[PbnI3n+1] (n = 1 and n = 2). We show how thermally driven lattice contraction and changes in crystal packing affect their characteristic absorption and photoluminescence. These findings provide new insights for functional perovskites’ rational design, highlighting the possibility to tune the structural properties through external stimuli to control their functionalities on-demand.